Exploring Inflation Dynamics with the Phillips Curve in Türkiye: Evidence from the Markov Regime Switching Model - Ali İlhan (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
Unlike in many advanced and emerging market economies, inflation was already a problem for the Turkish economy before the COVID-19 pandemic. During the 1990s, Türkiye experienced severe inflation, which reached three digits in some months. Although inflation was reduced to single digits in the 2000s through a successful disinflation program under an implicit inflation targeting framework with a flexible exchange rate regime, price stability became a problem again after the global financial crisis. Inflation gradually increased during the 2010s and became out of control after late 2021. This study aims to explore inflation dynamics in Türkiye using the Phillips curve framework for different inflation environments. To this end, the Phillips curve equation, augmented with the exchange rate and oil prices, is estimated using the Markov regime switching model between January 2006 and September 2023. Two regimes are identified in the sample, namely low- and high-inflation regimes. According to the estimation results, the Phillips curve is invalid in both regimes. The unemployment gap is statistically insignificant despite its negative impact on current inflation. The increasing coefficient of backward inflation in the high regime reflects the resurgent indexation behavior, which was dominant before inflation targeting was introduced in Türkiye. The positive impact of oil prices is only statistically significant in the low regime. While an increase in the exchange rate significantly raises inflation in both regimes, the effect is greater in the high-inflation regime. These empirical findings indicate that the primary issues for controlling inflation in Türkiye are inflation inertia and exchange rate stability.